More transit of hydrocarbons in our sea: they endanger our foods of marine origin - Quispe-Villanueva, Manuel S. (2022)
We are currently heading towards a change in the energy source of oil and its derivatives towards the use of wind, solar, hydrogen and hydroelectric energy, among others. However, our country continues to grant permits for the exploration and exploitation of hydrocarbons in our sea. For this reason, the purpose of this review is to provide scientific evidence to generate the best opinion criteria in the population regarding the license granted by the Ministry of Energy and Mines to the companies Perupetro and Tullow Peru Limited for the exploration and drilling of hydrocarbons. in front of the Ancash region in lots Z-67 and Z-68. The search was carried out in the Medline (PubMed), Web of Science, university repositories and the Concytec library. For all cases, the keywords have been used: oil or hydrocarbon spill. The following conclusions were reached: The few investigations regarding the impact of hydrocarbons in our Peruvian sea make it difficult to be clear about their effects on the marine environment and on its hydrobiological resources. And the increase in the transit of vessels with hydrocarbons in our sea increases the chances of oil spills in our sea, endangering our food of marine origin.